2013
DOI: 10.1039/c3nr04257j
|View full text |Cite
|
Sign up to set email alerts
|

Noble metal alloy clusters in the gas phase derived from protein templates: unusual recognition of palladium by gold

Abstract: Matrix assisted laser desorption ionization of a mixture of gold and palladium adducts of the protein lysozyme (Lyz) produces naked alloy clusters of the type Au 24 Pd + in the gas phase. over all other clusters. Gas phase cluster formation occurs from protein adducts where Au is in the 1+ state while Pd is in the 2+ state. The creation of alloys in the gas phase is not affected whether a physical mixture of Au and Pd adducts or a Au and Pd co-adduct is used as the precursor. The formation of Au cores and AuPd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…The overall surface structure of the protein shows nearly spherical geometry with mean diameter (considering three-dimensional orientation) of about 3.9 nm. 45,47 We have studied the formation and growth of gold clusters using SAXS, and the data were compared with mass spectrometric evolution of the clusters within the protein. It is known from a previous study that when protein interacts with Au…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall surface structure of the protein shows nearly spherical geometry with mean diameter (considering three-dimensional orientation) of about 3.9 nm. 45,47 We have studied the formation and growth of gold clusters using SAXS, and the data were compared with mass spectrometric evolution of the clusters within the protein. It is known from a previous study that when protein interacts with Au…”
Section: Resultsmentioning
confidence: 99%
“…Thus, considering the above observations, we have used the sphere model in the subsequent analyses. 45,47 3.3. Evolution of Gold Cluster in Lyz.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed that the cluster nucleation occurred in the vicinity of the protein, in the gas phase, leading to the formation of magic numbered Au clusters. Later, naked alloy clusters of the type Au 24 Pd + were also detected in the gas phase using a similar approach . A recent perspective article by Rao and Pradeep summarizes advances in the synthesis of atomically precise QCs of silver, gold, and their alloys with special emphasis on silver QCs.…”
Section: Common Synthetic Approachesmentioning
confidence: 99%
“…In addition to the thiolate‐protected Au‐Pd NCs in solution, naked Au‐Pd NCs in gas phase and phosphine‐protected Au‐Pd NCs in solution have also been studied extensively in the research community . Moreover, many studies have indicated the excellent catalytic activities of Au‐Pd and Au‐Pt NCs .…”
Section: Synthesis Of Monodisperse And/or Luminescent Bi‐mncsmentioning
confidence: 99%